Investigating the role of micrornas in mammalian developmental transitions - Bailey, Laura (The University of Edinburgh, 2012)
miRNAs are short, non-coding RNA molecules that regulate gene expression posttranscriptionally through inhibition of translation and/or mRNA degradation. Mammalian development is a complex series of developmental transitions, which relies on accurate spatial and temporal regulation of gene expression and we are interested in the role that miRNAs may play in these developmental transitions. An initial objective was to establish which, if any, miRNAs were dynamically regulated in a cell model of an early developmental transition, and to establish whether differential expression of any particular miRNA played a functional role in this developmental process. Having established a role for specific miRNAs, further objectives were to assess the reliability of current miRNA-mRNA target identification procedures and to assess the general role of miRNAs in cellular differentiation. In order to explore the roles of miRNAs during an early developmental transition, an embryonic stem (ES) cell model of trophectoderm differentiation was used. In this model system the expression of the key ES cell regulatory gene, Oct4, can be conditionally repressed, which induces the ES cells to differentiate down the trophectoderm lineage. The expression of microRNAs was profiled in this model system by cloning and sequencing of small RNAs. This approach identified miRNAs that were dynamically regulated during differentiation. The expression patterns of differentially regulated miRNAs were confirmed by miRNA northern analysis. The miRNA profiling data showed that mmu-miR-294 and mmu-mir-295 are expressed at similar levels in ES cells and differentiated cells, which disagrees with previous reports that these miRNAs are ES cell specific. Several of the miRNAs with higher expression levels in differentiated cells are encoded within a placental-enriched polycomb group gene, Sfmbt2, suggesting an important role for these miRNAs in extraembryonic development. One of the miRNAs that was expressed at higher levels in ES cells than in differentiated cells, mmu-miR-92a, was shown to play a role in regulation of cell proliferation. Three current methods of identifying miRNA targets were assessed. A sequencebased method using the web-based utility miRecords, which amalgamates results from numerous target prediction databases, was used to generate lists of potential targets of the Sfmbt2 miRNA cluster and of mmu-miR-92a. Amalgamating results from multiple target prediction programs may improve the likelihood that the predicted targets are real. Exemplifying this, the single mmu-miR-92a target that was predicted by six different target prediction programs had been previously experimentally verified. An experimental method of identifying direct miRNA targets, PAR-CLIP, was investigated but proved technically limiting for routine use in the laboratory. A proteome-based experimental method for identifying potential miRNA targets, called SILAC, was successfully used to identify proteins that were differentially expressed in the cell model of trophectoderm differentiation. Differential expression of two of these proteins, CTBP2 and CKB, was confirmed by western analysis. miRecords was then used to assess whether the differentially expressed proteins were likely to be targets of the differentially expressed miRNAs that had been identified in the miRNA profiling analysis. The general role of miRNAs in cell differentiation was investigated using a cell line that does not express miRNAs. This ES cell line is deficient for the miRNAprocessing enzyme DGCR8, which results in loss of expression of mature miRNAs in these cells. Compared to wild type ES cells, miRNA-deficient ES cells expressed normal levels of the ES cell marker genes Oct4 and Sox2 but elevated levels of Nanog. In contrast to wild type ES cells, miRNA-deficient ES cells did not upregulate the mesoderm marker gene Brachyury during embryoid body differentiation and showed reduced upregulation of the endoderm marker gene Gata6. These findings suggest that miRNAs are not required for maintenance of pluripotency, but are essential for proper ES cell differentiation. The results presented in this thesis show that miRNAs are dynamically expressed during a mammalian developmental transition and are involved in regulating early developmental processes. We believe that miRNAs act as an additional level of genetic regulation to ensure canalisation during embryonic development.
Keywords: MicroRNA; embryonic stem cells; development; post transcriptional; genetic regulation